STRATEGI INDONESIA UNTUK MENGURANGI SAMPAH PLASTIK DI LAUT MELALUI KEANGGOTAAN KERJASAMA REGIONAL COORDINATING BODY IN THE SEAS OF EAST ASIA (COBSEA) - Bhima Agung Segoro; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The fact that Indonesia is the country that contributing marine plastic debris is the second largest in the world were indeed unavoidable again. The problem of marine plastic debris a threat so real and very contradictory for Indonesia who want to realizing the realization of Indonesia's Vision as a World Maritime Axis Country.Referring to the increasing intensity of marine plastic debris which gets higher throughout the year and not balanced by treating good of plastic waste, several strategies to reducing marine plastic debris are very much needed by Indonesia today, one of them by joining and conducting regional cooperation with the Coordinating Body on the Seas of East Asia (COBSEA). This research uses the theory of Sustainable Development Goals and supported by the concept of Maritime Security. This study also uses descriptive qualitative research methods and uses the Nation State as a level analysis . Research data is obtained through literature review and all research data derived directly from government official websites and related regional environmental agencies. Based on the results from analyzing of the researchers, it can be concluded that the Indonesian government's strategy to reduce marine s by joining and conducting regional cooperation with the Coordinating Body on the Seas of East Asia (COBSEA) is to create and execute the Regional Action Plan of Marine Litter (RAP-MALI ) and dividing again the action plan into several systematic and directed strategies. This research proves that the Indonesian government has a strong commitment and is trying to reduce marine plastic debris in order to realize Indonesia as the World's Maritime Axis.Keywords: Coordinating Body on the Seas of East Asia (COBSEA), Marine Plastic Debris, Strategy, World’s Maritime Axis, Regional Cooperation.